Empowering sustainability : Viability analysis of a floating photovoltaic system at Gulshan Lake - Maruf, Md Hasan; Moli, Farzana Akter; Noyon, Nayem Ahmed; July, Sameya Afrin; Islam, Md Imamul; Shihavuddin, Asm S.M. (Institute of Electrical and Electronics Engineers Inc, 2023)
The world's increasing energy demands have intensified the need for renewable energy sources. In response to the land constraints posed by ground-mounted solar installations, Floating Photovoltaic (FPV) has emerged as a promising solution. This study focuses on exploring the feasibility of building floating solar panels in Bangladesh, with an experimental investigation conducted on Gulshan Lake, an urban water body located in Dhaka city. The lake is facing mounting pollution and degradation due to rapid urbanization, industrialization, and population growth. Consequently, the pursuit of sustainable development and clean energy has led to a keen interest in renewable energy sources, particularly floating PV systems. The paper thoroughly considers the technical, financial, and environmental aspects involved in the construction of such a system during the feasibility analysis. The design of the plant and tariff are meticulously carried out using the HOMER software, and the study calculates the optimal cost of electricity for the FPV power plant manually, projecting figures for 20 and 25-year periods at BDT 10.92 and BDT 7.23, respectively. The same calculations performed with the HOMER software yield slightly higher values of BDT 12.17 and BDT 11.87 for the same time spans. Moreover, the paper highlights the cost-effectiveness of the designed PV system.